Assessment of Oral Poliovirus Vaccine Viability and Titer at Delivery Points in Kinshasa, the Democratic Republic of the Congo: Implications for Cold Chain Management - Gracia Kashitu-Mujinga; Anguy Makaka-Mutondo; Meris Matondo-Kuamfumu; Fabrice Mambu-Mbika; Junior Bulabula-Penge; Trésor Kabeya-Mampuela; Frida Nkawa; Grace Wanet-Tayele; Bibiche Nsunda-Makanzu; Pierre Nsele-Muntatu; Lusamba Kabamba; Antoine Nkuba-Ndaye; et al. (Vaccines)
Background: Poliomyelitis is a vaccine-preventable disease, with oral poliomyelitis vaccines (OPVs) and injectable poliomyelitis vaccines. In the Democratic Republic of the Congo (DRC), circulating vaccine-derived polioviruses (VDPVs) persist due to intrinsic and extrinsic factors, including the quality of the cold chain, which may make the vaccines less effective. This study’s objective was to evaluate the cold chain’s quality of OPVs and its effect on the vaccine’s viability and potency at different levels in health systems in Kinshasa. Methods: A cross-sectional study was conducted in Kinshasa, collecting OPVs at different levels of the health pyramid. Vaccine viability was assessed by cell culture using a modified World Health Organization (WHO) protocol, and the viral titer was determined using the Karber formula. The vaccine titer was classified as “very good”, “good”, or “poor” according to the WHO standard’s viral titer. Results: A total of 53 vaccines were collected and analyzed, compressing 38 bivalent oral poliomyelitis (bOPV) vaccines and 15 novel oral poliomyelitis vaccines, type 2 (nOPV2). The viral titer ranged from log105.8 to log 107.3 and from log105.4 to log108.9 for the nOPV2 and the bOPV, respectively. Of these 53 vaccine samples, 10% of the bOPVs showed viral titers below the recommended WHO threshold (>106 CCID50/dose), 100% of the nOPV2 had viral titers within the WHO standards (>105 CCID50/dose), and a significant decline in the viral titer was observed for both types of vaccines (nOPV2 and bOPV) as the distribution progressed along the level of the health pyramid. Conclusions: This study demonstrated that the viral titer of OPV declined from central to peripheral areas in routine and campaign strategies in Kinshasa.